(untitled) (Eurasian Medical Research Periodical, 2023)
Diagnosis and treatment of chronic coronary heart disease (CHD) is well developed, but there are often difficulties in managing patients with comorbid diseases. A very common chronic kidney disease (CKD) occupies a special place among comorbidities. The cause of death in patients with kidney dysfunction is significantly more often CHD than end-stage renal disease (ESRD). In recent years, cystatin C has been considered as an early marker for assessing the functional state of the kidneys and cardiovascular risk, the level of which, unlike creatinine, does not depend on gender, age, race, and muscle mass